How do Spanish and English Languages Determine Young Afro-Caribbean Descendants’ Identity? - Vargas Jiménez, Grettel (Revista de Lenguas Modernas, 2017)
Considering the linguistic diversity Afro descendants experience in Limón province, this research project is focused on a qualitative ap proach and basically it portrays an ethnographic perspective about nineteen (19) young Afro descendant students at Saint Mark’s high school in downtown Limón, and the same number of older Afro-Caribbeans in downtown Limón and surroundings in order to establish comparisons and draw conclusions in regards to how they define themselves: as native speakers of Spanish, as native speakers of English, as native speakers of Limón Creole, or as multilinguals, and the role of this badge of identification in the process of construction of their identity. Likewise, this ethnographic design tries to describe and analyze the ideas, beliefs, behaviors, knowledge and experiences of both Afro-Caribbean groups in relation to language and interaction in different contexts and situations. Considerando la diversidad lingü.stica que experimenta la población afrodescendiente de la provincia de Limón, esta investigación se basa en un enfoque cualitativo, el cual analiza y compara, desde una perspectiva etnográfica, a un grupo de diecinueve jóvenes estudiantes afrodescendientes del Colegio San Marcos, en Limón, con un grupo de igual número de adultos afrocaribeños del centro de Limón y sus alrededores, con el propósito de establecer comparaciones y conclusiones acerca de cómo se definen ellos: como nativos hablantes del idioma español, como nativos hablantes del idioma inglés, cómo nativos hablantes del criollo limonense o como multilingües, y el rol que desempeñan estos lenguajes en la formación de su identidad. Asimismo, este diseño etnográfico trata de describir y evaluar las percepciones, comportamientos, conocimientos y experiencias de ambos grupos en relación con el lenguaje en diversos contextos y situaciones.